Normal saline and lung recruitment with paediatric endotracheal suction (NARES): A pilot, factorial, randomised controlled trial. Issue 6 (November 2021) - Schults, Jessica A.; Cooke, Marie; Long, Debbie; Schibler, Andreas; Ware, Robert S.; Charles, Karina; Irwin, Adam; Mitchell, Marion L.
Abstract: Background/objective: Endotracheal suction is one of the most common and harmful procuedres performed on mechanically ventilated children. The aim of the study was to establish the feasibility of a randomised controlled trial (RCT) examining the effectiveness of normal saline instillation (NSI) and a positive end-expiratory pressure recruitment manoeuvre (RM) with endotracheal suction in the paediatric intensive care unit. Methods: Pilot 2 × 2 factorial RCT. The study was conducted at a 36-bed tertiary paediatric intensive care unit in Australia. Fifty-eight children aged less than 16 years undergoing tracheal intubation and invasive mechanical ventilation. (i) NSI or no NSI and (ii) RM or no RM with endotracheal suction . The primary outcome was feasibility; secondary outcomes were ventilator-associated pneumonia (VAP), change in end-expiratory lung volume assessed by electrical impedance tomography, dynamic compliance, and oxygen saturation-to-fraction of inspired oxygen (SpO2 /FiO2 ) ratio. Results/Findings: Recruitment, retention, and missing data feasibility criteria were achieved. Eligibility and protocol adherence criteria were not achieved, with 818 patients eligible and 58 enrolled; cardiac surgery was the primary reason for exclusion. Approximately 30% of patients had at least one episode of nonadherence. Children who received NSI had a reduced incidence of VAP; however, this did not reach statistical significance (incidence rate ratio = 0.12, 95% confidence interval = 0.01–1.10; p = 0.06). NSI was associated with a significantly reduced SpO2 /FiO2 ratio up to 10 min after suction. RMs were not associated with a reduced VAP incidence (incidence rate ratio = 0.31, 95% confidence interval = 0.05–1.88), but did significantly improve end-expiratory lung volume at 2 and 5 min after suction, dynamic compliance, and SpO2 /FiO2 ratio. Conclusion: RMs provided short-term improvements in end-expiratory lung volume and oxygenation. NSI with suction led to a reduced incidence of VAP; however, a definitive RCT is needed to test statistical differences. A RCT of study interventions is worthwhile and may be feasible with protocol modifications including the widening of participant eligibility.